Human‐on‐a‐Chip Systems: Long‐Term Electrical and Mechanical Function Monitoring of a Human‐on‐a‐Chip System (Adv. Funct. Mater. 8/2019). (19th February 2019) - Oleaga, Carlota; Lavado, Andrea; Riu, Anne; Rothemund, Sandra; Carmona‐Moran, Carlos A.; Persaud, Keisha; Yurko, Andrew; Lear, Jennifer; Narasimhan, Narasimhan Sriram; Long, Christopher J.; Sommerhage, Frank; Bridges, Lee Richard; et al.
Abstract : In article number1805792, James J. Hickman and co‐workers describe human‐on‐a‐chip systems that aim to reproduce physiologic aspects of the human body by merging human tissue with engineered BioMEMs systems to emulate clinical parameters. This technology opens a broad spectrum of possibilities to better predict the human outcome without having to rely on animal experimentation.